2022
DOI: 10.1039/d1gc04783c
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-assisted phenolation of acid-insoluble Klason lignin and its application in adhesion

Abstract: In this study, a microwave irradiation is employed for the phenolation of acid-insoluble Klason lignin. Microwave irradiation significantly reduces the reaction temperature (180 →100 °C) and time (6 h →...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…Lignin modifications, including methylation, demethylation, , hydrolytic depolymerization, , and phenolation, , are extensively applied in lignin research studies. As one of the most efficient ways to improve the reactivity of lignin, phenolation efficiently increases lignin’s phenolic hydroxyl group (Ph-OH) contents and active sites, which facilitates the utilization of technical lignins. , Lignin phenolation under acidic conditions is the most commonly used method. Under strongly acidic conditions, phenols could be grafted on lignin by the electrophilic substitution between phenol and the α or γ-carbocation at a low pH value after dehydration, and then because of the cleavage of β–O–4, Cα–Cβ, and Cβ–Cγ bonds, new reactive sites are generated by releasing formaldehyde (Figure ). The break of the side chain linkages leads to a reduction in the molecular weight of the phenolated lignin, and it is found that the reaction activity of the resultant lignin has been significantly improved due to the increase of Ph-OH groups. , For instance, phenolated lignins are excellent feedstocks or additives to produce various functional materials with improved performances, such as lignin-phenol-formaldehyde resin adhesives, , thermo-sensitive gel, polyurethane foams, biophenol-hydroxymethylfurfural resins, and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…Lignin modifications, including methylation, demethylation, , hydrolytic depolymerization, , and phenolation, , are extensively applied in lignin research studies. As one of the most efficient ways to improve the reactivity of lignin, phenolation efficiently increases lignin’s phenolic hydroxyl group (Ph-OH) contents and active sites, which facilitates the utilization of technical lignins. , Lignin phenolation under acidic conditions is the most commonly used method. Under strongly acidic conditions, phenols could be grafted on lignin by the electrophilic substitution between phenol and the α or γ-carbocation at a low pH value after dehydration, and then because of the cleavage of β–O–4, Cα–Cβ, and Cβ–Cγ bonds, new reactive sites are generated by releasing formaldehyde (Figure ). The break of the side chain linkages leads to a reduction in the molecular weight of the phenolated lignin, and it is found that the reaction activity of the resultant lignin has been significantly improved due to the increase of Ph-OH groups. , For instance, phenolated lignins are excellent feedstocks or additives to produce various functional materials with improved performances, such as lignin-phenol-formaldehyde resin adhesives, , thermo-sensitive gel, polyurethane foams, biophenol-hydroxymethylfurfural resins, and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…These two peaks could be attributed to the aromatic C–H bending of phenols attached to the ortho and para positions of the lignin moiety, respectively. 8,30,34 The successful amination of PL can be confirmed by a C–N stretching peak of tertiary amine at 1257 cm −1 , along with –CH 3 symmetrical deformation at 1384 cm −1 and –CH 2 – deformation at 1457 cm −1 from the diethylamine group. Additionally, there are new peaks at 882 and 910 cm −1 , corresponding to the aliphatic C–H bond in –N(CH 2 CH 3 ) 2 and the newly formed –CH 2 – between lignin and –N(CH 2 CH 3 ) 2 .…”
Section: Resultsmentioning
confidence: 92%
“…147,150 When phenolation of Klason lignin was performed using the microwave heating method, the phenolation rate increased with a higher phenol/lignin ratio. 151 Moreover, with an increase in the phenol/lignin ratio, the molecular weight and T g of the phenolated lignin decreased, which was attributed to the enhanced decomposition of lignin and the inhibition of its cross-linking reaction. In addition, owing to the increase in the number of phenol groups and the decrease in molecular weight, phenolated lignin showed higher solubility in tetrahydrofuran and methanol than Klason lignin.…”
Section: Functionalization Strategies For Ligninmentioning
confidence: 99%
“…In addition, owing to the increase in the number of phenol groups and the decrease in molecular weight, phenolated lignin showed higher solubility in tetrahydrofuran and methanol than Klason lignin. 151 When lignin extracted from wheat straw was phenolated, the high acid charge was conducive to the introduction of phenol. 147 For the temperature of phenolation, in the range of 70 °C to 110 °C, the degree of phenolation increased with an increase in temperature, which can be explained by the solubility of lignin in phenol.…”
Section: Functionalization Strategies For Ligninmentioning
confidence: 99%